2011
DOI: 10.1371/journal.pone.0020501
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Positive Lysosomal Modulation in Alzheimer's Disease Transgenic Mouse Models

Abstract: Alzheimer's disease (AD) is an age-related neurodegenerative pathology in which defects in proteolytic clearance of amyloid β peptide (Aβ) likely contribute to the progressive nature of the disorder. Lysosomal proteases of the cathepsin family exhibit up-regulation in response to accumulating proteins including Aβ1–42. Here, the lysosomal modulator Z-Phe-Ala-diazomethylketone (PADK) was used to test whether proteolytic activity can be enhanced to reduce the accumulation events in AD mouse models expressing dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
96
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(109 citation statements)
references
References 66 publications
11
96
1
1
Order By: Relevance
“…Earlier studies reported that cathepsin D can have a survival or apoptotic effect depending on the subcellular localization and activity of the enzyme. If the levels and activity of the enzyme are increased within the lysosomes, it may represent an adaptive response to protect cells against toxic insults (39,43,70,71), whereas an enhanced activity and cytosolic levels of the enzyme can lead to cell death either directly or indirectly via cytochrome c release from mitochondria (6 -8). This phenomenon has been described under in vitro paradigms using a variety of toxic insults (29,44,(73)(74)(75)(76)(77) and in some animal models of neurodegenerative disorders (78 -80).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies reported that cathepsin D can have a survival or apoptotic effect depending on the subcellular localization and activity of the enzyme. If the levels and activity of the enzyme are increased within the lysosomes, it may represent an adaptive response to protect cells against toxic insults (39,43,70,71), whereas an enhanced activity and cytosolic levels of the enzyme can lead to cell death either directly or indirectly via cytochrome c release from mitochondria (6 -8). This phenomenon has been described under in vitro paradigms using a variety of toxic insults (29,44,(73)(74)(75)(76)(77) and in some animal models of neurodegenerative disorders (78 -80).…”
Section: Discussionmentioning
confidence: 99%
“…Intraperitoneal administration of pepstatin A has been shown to be beneficial for experimental colitis and bone mineralization (101,102), but it needs to be determined whether intracerebroventricular administration of the inhibitor can mitigate NPC pathology. Given the evidence that selective cathepsin B inhibitor can reduce brain A␤ levels/ deposition and improve cognitive behavioral deficits in animal models of Alzheimer disease (72,103), it is likely that the availability of rather selective and potent cathepsin D inhibitors that can cross the blood-brain barrier may provide a new therapeutic opportunity in the treatment of NPC pathology.…”
Section: Discussionmentioning
confidence: 99%
“…28 Cathepsin B has also been implicated in the cleavage of Ab 1-42 into less amyloidogenic species. 20,29 A wide variety of agents are listed in Table 1 that have been found to elicit positive lysosomal modulation. Chloroquine and bafilomycin A1, the latter being an adenosine triphosphatase (ATPase) blocker that also disrupts lysosomal pH, both cause lysosomal stress resulting in hydrolase responses.…”
mentioning
confidence: 99%
“…Compounds that modulate lysosomal fusion include potential cystatin B and C antagonists [127], lysosomal cathepsin B modulators [212], and GSK-3β inhibitors, such as lithium, valproate, and NP12 [180,181]. Genetic deletion of cystatin B and C has been shown to improve neurological deficits and restore autophagic dysfunction in the TgCRND8 and hAPP-J20 mouse models of AD [127,213].…”
Section: Trehalosementioning
confidence: 99%
“…Cathepsin B is a lysosomal/endosomal enzyme with neuroprotective properties based on its protease activity, and in particular, its Aβ 1-42 cleavage function [219]. Z-Phe-Aladiazomethylketone, a positive modulator of cathepsin B activity, reduces Aβ levels in 10-11-month-old APP mice with Swedish and Indiana mutations (APP Swe/Ind ) and in 20-22-month-old APP swedish /PS1ΔE9 mice, protects against synaptic degeneration, and mitigates behavioral deficits [212]. Similarly, cathepsin D, another lysosomal/endosomal enzyme, has been implicated in clearance of Lewy bodies in PD [220].…”
Section: Trehalosementioning
confidence: 99%